Um modelo de avaliação da competitividade logística industrial - Rocha, Augusto Cesar Barreto (2009)
This work presents a competitiveness evaluation model to industrial logistic. To do this realizes a bibliographic revision of performance evaluation techniques used to manage logistic processes published in scientific papers from 1997 thru 2008. Moreover presents management model to supply chains such as SCOR and approaches to industrial location. Based in an exploratory research at a Brazilian Industrial Pole in 70 Brazilian companies, verifies which are the performance indicators mostly used to evaluate the logistic competitiveness. At the end presents an evaluation model to logistic competitiveness in industries and presents discussions about the praxis in performance indicators to logistics.